Vertex-weighted Wiener polynomials for composite graphs - Došlić, Tomislav (Ars mathematica contemporanea, 2008)
Recently introduced vertex-weighted Wiener polynomials are a common generalization of both vertex-weighted Wiener numbers and ordinary Wiener polynomials. We present here explicit formulae for vertex-weighted Wiener polynomials of the most frequently encountered classes of composite graphs.
Keywords: matematika; teorija grafov; Wienerjev indeks; Wienerjev polinom; Wienerjevo število